The relationship between NFÎºÎ²-p65 and PGE2 gene expression in osteoarthritis synoviocyte cells after mesenchymal stem cell Wharton Jelly Treatment - Vivi Sofia (Pharmaciana, 2020)
The genes involved in cartilage degradation in the pathogenesis of osteoarthritis ( OA) are the Nuclear Factor Kappa Beta (NFÄ¸Î²) gene, which plays a vital role in modulating cartilage damage involving activation of pro-inflammatory cytokines, including prostaglandin E2 (PGE2). This pure experimental research aimed at analyzing the relationship between the expression of NFÄ¸Î² genes after administration of mesenchymal stem cells in osteoarthritis synoviocytes in vitro from Wharton's Jelly (WJ-MSCs). The samples were isolated from synovial tissues of patients with osteoarthritis who underwent Total Knee Replacement (TKR) surgery and then divided into six treatment groups, each with four replicates. Groups I and II were the synoviocyte-control classes of 24h and 48h (synoviocytes, incubated for 24 and 48 hours respectively). Groups III and IV were control groups of 24h and 48h WJ-MSCs (mesenchymal stem cells derived from the Wharton's Jelly, incubated for 24 and 48 hours respectively). Finally, Groups V and VI were the 24-hour and 48-hour co-cultural treatment groups (synoviocyte co-culture and WJ-MSCs, Incubated, for 24 and 48 hours respectively). Using qPCR, PGE2 gene and NF NFÎºÎ² gene expressions were observed in each population. Tests showed 0.61 and 0.61, respectively, after the administration of WJ-MSCs, the expressions of the NFÎºÎ²-p65 and PGE2 genes in the 24h classes. In the 48h group, meanwhile, both numbers fell to 0.15 and 0.47, respectively. These indicate a strong correlation between the NFÎºÎ²-p65 gene and PGE2 gene expressions in OA synovial cells after the administration of MSC-WJ (r = 0.903).